Entrepreneurship and creation of new business: perceptions, behaviours and attitudes of students of a portuguese higher education institution - Ribeiro, Maria Isabel (2017)
Entrepreneurship encompasses the creation of new businesses and the development of new business opportunities in existing organizations. This work intends to understand the perceptions and attitudes of Portuguese students from a public institution of higher education regarding the creation of new businesses. A survey was conducted in 2014 and 2015 using an accidental sample of 336 students. The data were analysed using SPSS 22.0. The respondents believe that entrepreneurship contributes to the creation and growth of employment, that an entrepreneur is someone who has aradically new idea for creating a new business, and 46% of them could imagine themselves creating their own business. For these students, the probability of being able to create a successful business is, on average, 47%, and the right age to do it is 28 years old. Around 49% of the respondents are interested in creating a new business from an idea, mostly because it allows personal independence. Furthermore, despite being very optimistic as regards the start-up survival rate, students show little proactivity. Indeed, the majority of the respondents consider that business creation would be encouraged if the teaching institution provided ideas for students willing to create new businesses.